Everywhere - Brooks, Bruce (New York : Harper & Row, 1990)
Afraid that his beloved grandfather will die after suffering a heart attack, a nine-year-old boy agrees to join ten-year-old Dooley in performing a mysterious ritual called soul switching.
Faculty.
Keywords: Grandfathers -- Fiction; Death -- Fiction